German Wage Underpayment: An Investigation into Labor Market Inefficiency and Discrimination - Peter Dawson; Timothy Hinks; Duncan Watson (Vierteljahrshefte zur Wirtschaftsforschung, 2001)
Using stochastic panel wage frontiers, this paper estimates the relative underpayment of females and males in the reunified Germany. The estimates are initially applied to discrimination analysis. It finds that females have higher underpayment and that the male-female differential increased over the period 1991-1993. However, the paper suggests that the estimates of underpayment reflect other concerns, such as dynamic monopsony. Labor market inefficiency must be taken into account before discrimination analysis is possible.
Keywords: 330; Arbeitsmarkt; Lohnstruktur; Fraueneinkommen; Deutschland